Aphasia and age of acquisition: are early-learned words more resilient?. Issue 11 (1st November 2016) - Brysbaert, Marc; Ellis, Andrew W.
ABSTRACT: Background : Aphasia patients can produce some words reliably but have difficulty retrieving other words. In this article we review one of the variables that have been proposed to explain which words remain available. Aims : Age of acquisition (AoA) refers to the age at which people learn a word. We review the evidence indicating that early-learned words remain more accessible than late-learned words in acquired aphasia. We examine the most likely mechanisms. Methods and procedures : We review the various studies that investigated the effect of AoA on word retrieval in acquired aphasia and in dementia. We link the findings to differences in processing efficiency in healthy individuals and to the mechanisms that have been proposed there to explain the differences. We also have a critical look at the methods used in various studies and investigate which precautions must be taken to advance our knowledge about the AoA effect. Outcomes and results : We argue that the effects of AoA and frequency are a result of the brain acquiring information over time in an incremental manner, improving with practice and possibly showing a decline in plasticity as the brain ages and more information becomes stored. Because AoA is yoked to frequency, an AoA effect is likely to be accompanied by a frequency effect of roughly the same size. In addition, AoA has a unique effect on the ease with which the correct verbal response can be retrieved in a naming task based on semantic input, such as object naming. Conclusions : Words learned early in life are more likely to be retained in acquired aphasia than words learned later in life. The finding that AoA has a unique effect on the ease with which the correct verbal response can be retrieved in object naming may be due to the organisation of the semantic system, such that early acquired meanings are richer, more accessible and more robust against brain damage. Alternatively, it may be due to the way in which semantic information is translated in verbal output. To further our knowledge, researchers are encouraged to use more powerful regression designs with more stimuli, and to include better measures than has been done in the past. We also argue that more information can be gathered by not limiting the research to picture naming.